(3fRgI GdCYjf GdfhGXQ aj Yde GdhLhg hGdfXGFQs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s
(3ChdgG (B:s
(3ef GdTQ hGdaJf dGfgG eRjdI dJYbd GdPi gh edGc GdGTjGA abO jchf ai GdfaS GdhLd s
(3BNQgG (B:s
(3HGf eG PcQ ef GdYah hGdSde eeG dGjSJWGY GfbVGA acja HGJNGP HOGjI s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1940s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs